Quality Improvement Design on Sales Website Using Fuzzy Quality Function Deployment (FQFD) Method - Anindita Dewi Artanti; Yati Rohayati; Fakhirah Nur Alifah (Institut Teknologi Sepuluh Nopember, 2020)
PT. XYZ is a company engaged in fashion which manufactures and sells its own products to consumers. The company sells through various online media including its own website and several marketplace media. However, their consumers make more online purchases through the marketplace than the website, which makes it difficult because the company can only use purchases from the website to obtain complete customer data needed to explore customer behavior. This research will be done using the Fuzzy QFD method to improve the quality of online sales service through the website based on the identified weaknesses of the company website that causes consumers to avoid making online purchases through the website. Fuzzy QFD is a QFD method integrated with fuzzy logic which aims to reduce the vagueness or obscurity of subjective judgments to improve calculation accuracy. The results of this research are 5 technical requirement from FQFD 1st iteration and critical part from 2nd iteration which are expected to produce recommendations needed by company to improve the quality of online sales services through its website based on a more objective and accurate data.